Cost-effectiveness of empagliflozin versus canagliflozin, dapagliflozin, or standard of care in patients with type 2 diabetes and established cardiovascular disease. Issue 1 (3rd May 2021) - Reifsnider, Odette S; Kansal, Anuraag R; Gandhi, Pranav K; Cragin, Lael; Brand, Sarah B; Pfarr, Egon; Fahrbach, Kyle; Ustyugova, Anastasia
Abstract : Introduction: Empagliflozin, a sodium-glucose co-transporter-2 (SGLT-2) inhibitor, is approved in the USA to reduce risk of cardiovascular (CV) death in adults with type 2 diabetes mellitus (T2DM) and established CV disease, based on EMPA-REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients) trial results. Empagliflozin reduced major adverse CV event (MACE) by 14%, CV death by 38%, and hospitalization for heart failure (HHF) by 35% vs placebo, each on top of standard of care (SoC). SGLT-2 inhibitors canagliflozin and dapagliflozin have also been compared with placebo, all on top of SoC, in CV outcome trials. In the CANVAS (Canagliflozin Cardiovascular Assessment Study) Program, canagliflozin reduced MACE by 14% and HHF by 33%. Dapagliflozin reduced HHF by 27% in the DECLARE-TIMI 58 trial (Multicenter Trial to Evaluate the Effect of Dapagliflozin on the Incidence of Cardiovascular Events). This analysis estimated the cost-effectiveness of empagliflozin versus canagliflozin, dapagliflozin, or SoC, in US adults with T2DM and established CV disease. Research design and methods: Individual patient-level discrete-event simulation was conducted to predict time-to-event for CV and renal outcomes, and specific adverse events over patients' lifetimes. Occurrence of events in EMPA-REG OUTCOME was estimated based on event-free survival curves with time-dependent covariates. An HR for canagliflozin or dapagliflozin versus empagliflozin on each clinical event was estimated from published CANVAS, DECLARE-TIMI 58, and EMPA-REG OUTCOME data using indirect treatment comparison. Public sources provided US costs and utilities. Results: The model predicted longer survival for empagliflozin versus canagliflozin, dapagliflozin, and SoC mainly due to direct reduction in CV death. Empagliflozin dominated canagliflozin, yielding more quality-adjusted life years (QALYs; 0.38) at a lower cost (−US306). Compared with dapagliflozin and SoC, empagliflozin yielded 0.50 and 0.84 incremental QALYs at US1517 and US27 539 incremental costs, yielding incremental cost-effectiveness ratios of US3054/QALY and US32 848/QALY, respectively. Conclusions: Empagliflozin was projected to dominate canagliflozin and be highly cost-effective compared with dapagliflozin and SoC using US healthcare costs.